Education on Kangaroo Mother Care (KMC) For Low Birth Weight (LBW) Babies in The Perinatology Room of Banten Regional Hospital - Annisa Ena; Siti Nurlela Ma'daniah; Zahrah Maulidia Septimar (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Introduction Infants are children aged 0-12 months, the toddler period is a golden period as well as a critical period for a child's growth and development. It is called the golden age because infancy is very short and cannot be repeated. (Nurjakiah et al., 2018). The Infant Mortality Rate (IMR) is one of the indicators commonly used to determine the level of public health, both at the provincial and national levels. One of the main causes of infant mortality is low birth weight. stated that this method is also useful in improving the function of the baby's organs, increasing the baby's immunity, and helping the baby's weight development. Based on the description above, kangaroo mother care has many positive impacts on the health of newborns, one of which is helping to increase weight in babies with LBW according to several studies that have been conducted. Purpose devotion public This is to determine the effect of Kangaroo Mother Care Health Counseling Method on LBW babies. Method which is used in devotion this , namely method quantitative with quasi-experimental, one group pre-test and post-test. The instrument used was the Kangoro questionnaire test. Data were analyzed using the Wilcoxon test. The results that is obtained shows that the results of the t-dependent test conducted in this study with a p-value of 0.002 (p value < alpha value 0.05) indicate a significant influence of kangaroo care method counseling on LBW babies on respondents' knowledge in the Perinatology Room of Banten Regional Hospital. So that can concluded method kangaroo can help improve weight in LBW.